System-level barriers to personal recovery in mental health: qualitative analysis of co-productive narrative dialogues between users and professionals - Nakanishi, Miharu (BJPsych Open, 2021)
BACKGROUND: No co-productive narrative synthesis of system-level facilitators and barriers to personal recovery in mental illness has been undertaken. AIMS: To clarify system-level facilitators and barriers to personal recovery of people with mental illness. METHOD: Qualitative study guided by thematic analysis. Data were collected through one focus group, which involved seven service users and three professionals. This group had 11 meetings, each lasting 2 h at a local research institute, between July 2016 to January 2018. RESULTS: The analysis yielded three themes: barriers inhibiting positive interaction within personal relationship networks, roots of barriers from mental health systems and the social cultural context, and possible solutions to address the roots. Barriers were acknowledged as those related to sense of safety, locus of control within oneself and reunion with self. The roots of barriers were recognised within mental health services, including system without trauma sensitivity, lack of advocacy support and limited access to psychosocial approaches. Roots from social cultural context were also found. There were no narratives relating to facilitators. A possible solution was to address the roots from systems. Social cultural change was called for that makes personalised goals most valued, with an inclusive design that overcomes stigma, to achieve an open and accepting community. CONCLUSIONS: The analysis yielded system-level barriers specific to each recovery process. Roots of barriers that need transformation to facilitate personal recovery were identified within mental health services. Social interventions should be further explored to translate the suggested social cultural changes into action.